Participation in International Environmental Agreements: The Role of Timing and Regulation - Michael Finus; Bianca Rundshagen (Fondazione Eni Enrico Mattei (FEEM), 2005)
We analyze the formation of self-enforcing international environmental agreements under the assumption that countries announce their participation either simultaneously or sequentially. It is shown that a sequential formation process opens up possibilities for strategic behavior of countries that may lead to inferior outcomes in terms of global abatement and welfare. We then analyze whether and under which conditions a regulator like an international organization, even without enforcement power, can improve upon globally suboptimal outcomes through coordination and moderation, given that recommendations must be Pareto-improving to all parties.
Keywords: C72; D70; H41; Q50; 330; International environmental agreements; Timing of participation decision; Coalition theory; Role of international regulator